24.–26. Juni 2005 in Leipzig: 10. wissenschaftliche Konferenz von Orbis Aethiopicus in Verbindung mit der 7th International Conference of Ethiopian Art: “Ethiopian Art – A Unique Cultural Heritage and a Modern Challenge” - Priess, Maija (Aethiopica, 2006)
Conference Review